Community Legal Education: Narcotics Prevention and Civil Rights Protection - Seri Mughni Sulubara; Yeni Irma Normawati; Harry Fauzi; Bohari Muslim; Amrizal (Institut Teknologi dan Bisnis Asia Malang, 2026)
Purpose: To empower communities through integrated legal education programs that prevent narcotics abuse, safeguard citizens' civil rights, and foster a safer, rights-respecting society. Method: This program employs a community-based, interactive legal education model to prevent narcotics abuse while protecting civil rights. It integrates preventive strategies like early awareness campaigns and rights education, drawing from successful Indonesian initiatives. Practical Applications: Practical applications of